2021
DOI: 10.1371/journal.pone.0249267
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of conflict of interest policies among organizations producing clinical practice guidelines

Abstract: Background Conflicts of interest (COI) jeopardize the validity of Clinical Practice Guidelines (CPGs). When the Institute of Medicine promulgated COI policies in 2011, few organizations met these requirements, but it is unknown if organizations have improved their policies since that time. We sought to evaluate current adherence to IOM standards of COI policies. Methods and findings We conducted a retrospective document review of COI policies and CPGs from organizations that published five or more CPGs betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Full COI disclosure without a financial threshold is standard for many guideline developing organizations. Only 6% of the guideline developing organizations specified a threshold for disclosure in 2021 22 . Literature review of COI policies by Ngo‐Metzger et al .…”
Section: Discussionmentioning
confidence: 99%
“…Full COI disclosure without a financial threshold is standard for many guideline developing organizations. Only 6% of the guideline developing organizations specified a threshold for disclosure in 2021 22 . Literature review of COI policies by Ngo‐Metzger et al .…”
Section: Discussionmentioning
confidence: 99%
“…Demographic data concerning physician gender, affiliations, positions in their affiliations, participation in clinical practice guidelines for pediatric cancers, and participation in the society board membership were collected from the official webpage of their affiliation and the JSPHO. All PHOs authoring clinical practice guidelines issued by the JSPHO between 2015 and 2020 (one year before and after the study period) were identified from the JSPHO webpage, as clinical practice guideline authors often received payments from companies before, during, and a few years after guideline publication 17,19–21 ; disclosure of these payments were strongly recommended by many societies 22–24 . As the name list of the JSPHO board member between 2016 and 2020 was not available, the PHOs who positioned in the JSPHO board member as of March 2022 were considered.…”
Section: Methodsmentioning
confidence: 99%
“…were identified from the JSPHO webpage, as clinical practice guideline authors often received payments from companies before, during, and a few years after guideline publication 17,[19][20][21] ; disclosure of these payments were strongly recommended by many societies. [22][23][24] As the name list of the JSPHO board member between 2016 and 2020 was not available, the PHOs who positioned in the JSPHO board member as of March 2022 were considered.…”
Section: Data Collectionmentioning
confidence: 99%
“…1 2 Physician researchers who receive industry payments are more likely to demonstrate results favourable to the companies funding them; 3 4 are more likely to prescribe drugs and use of medical devices produced by these companies, from statins 5 to opioids 6 to endoscopic 7 and orthopaedic devices; 8 and they may unduly influence other physicians by contributing to research that others use to guide their own clinical practice. [9][10][11][12][13][14][15][16] Industry payments to physicians therefore may bias healthcare providers' delivery of evidencebased medicine and interfere with their responsibilities to their patients.…”
Section: Introductionmentioning
confidence: 99%